Dual‐Emission of Fluorescence and Room‐Temperature Phosphorescence for Ratiometric and Colorimetric Oxygen Sensing and Detection Based on Dispersion of Pure Organic Thianthrene Dimer in Polymer Host. Issue 12 (11th April 2022) - Liu, Haichao; Pan, Guocui; Yang, Zhiqiang; Wen, Yating; Zhang, Xiangyu; Zhang, Shi‐Tong; Li, Weijun; Yang, Bing
Abstract: To improve room‐temperature phosphorescence (RTP) property, thianthrene (TA) is chemically modified into three intramolecular dimers (1TA1TA, 1TA2TA, and 2TA2TA) at different active sites. They all show dual‐emission of fluorescence and RTP after deoxygenation when they are dispersed in polymer matrix to form films. As for the RTP emission among their films, 2TA2TA shows the largest red shift peaking at 540 nm, the longest lifetime of 36.5 ms, and the highest RTP efficiency of 40.7%. These RTP characteristics enable 2TA2TA to act as a self‐referenced ratiometric and colorimetric probe for oxygen sensing and detection at low concentration. As a result, 2TA2TA exhibits the highest quenching efficiency of 98.4% and highest sensitivity ( K SV  = 13.32 KPa −1 ) for quantitative oxygen detection. Besides, these oxygen‐sensitive materials can also be used to study aerodynamics through a direct and visual observation of emission intensity/color distribution. Overall, the new‐generation optical probe will be developed in oxygen sensing and detection with high sensitivity, good reversibility, and reproducibility by using the pure organic materials with single‐molecule dual‐emission of fluorescence and RTP through the dispersion of the materials in polymeric host. Abstract : Dual‐emission of fluorescence and room‐temperature phosphorescence (RTP) are demonstrated for the dispersion of thianthrene dimers in polymer matrix. 2, 2′‐Bithianthrene shows the superior RTP properties featured with largely red‐shifted emission spectrum, high efficiency, and long lifetime. The dual‐emission of oxygen‐sensitive RTP and oxygen‐inert fluorescence is exactly employed for ratiometric and colorimetric optical oxygen sensor in low oxygen concentration range.